Spatially resolved spectroscopy across stellar surfaces: I. using exoplanet transits to analyze 3D stellar atmospheres - Dravins, Dainis; Ludwig, Hans-Günter (Astronomy and astrophysics, 2017)
Astronomy & Astrophysics (A&A) is an international journal which publishes papers on all aspects of astronomy and astrophysics
Gesehen am 10.10.2017